Doctoral Student Experience: The Supervisors' Perspective - Fiona Knight; Julia Taylor; Martyn Polkinghorne (MDPI AG, 2023)
This research considers the perceptions of doctoral supervisors relating to their experience of supervising students within a single case study university in the United Kingdom (UK). A survey of supervisors was undertaken that elicited quantitative and qualitative data, which were analysed and compared with the responses from postgraduate research students from the same institution, obtained through the annual national postgraduate research experience survey. This new understanding was important to elicit as it provided us with valuable insights into various aspects of the doctoral students' experience from a supervisory viewpoint, highlighting both strengths and areas that require improvement. By addressing the identified areas of concern, and building upon the areas of strength, the university will be able to enhance the doctoral supervision process, and so create a more positive and supportive postgraduate research environment in the future. One of the most interesting aspects to emerge from this research is the gap in perception between the supervisors' own views and those of their doctoral students, for example regarding communication. To greater understand the identified phenomena, it is recommended that this research should continue as a longitudinal study with the survey being repeated on a biennial basis.